Pengaruh Media Sosial, Perilaku FOMO (Fear of Missing Out), dan Penggunaan E-Money terhadap Perilaku Konsumtif Mahasiswa Pendidikan Ekonomi Universitas PGRI Wiranegara - Izzatul Mula; Sugeng Pradikto (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to analyze the influence of social media, FOMO (Fear of Missing Out) behavior, and the use of e-money on the consumptive behavior of students in the Economics Education Study Program at Universitas PGRI Wiranegara. The digital era has introduced new challenges in student financial management, particularly regarding the ease of accessing information and conducting digital transactions. The research employs a quantitative approach with an explanatory research design. The population consists of all active students in the study program, with a sample of 69 respondents selected through simple random sampling. Data were collected using a Likert-scale questionnaire and analyzed using multiple linear regression. The results indicate that social media, FOMO behavior, and e-money usage have a significant influence on students' consumptive behavior, both partially and simultaneously. This research contributes to a better understanding of the factors influencing consumer behavior in the digital age and can serve as a basis for developing more effective financial literacy programs for students.